Preliminary estimate of current ice thickness in the Dobšiná Ice Cave by means of geophysical and geodetic methods - PAŠTEKA, Roman; ZAHOREC, Pavol; ŠULEK, Ivan; ANDRÁSSY, Erik; PAPČO, Juraj; PUKANSKÁ, Katarína; NOGOVÁ, Ema; GODOVÁ, Dominika; ONDRÁŠOVÁ, Lenka; BÓDI, Jozef (Contributions to Geophysics and Geodesy, 2024)
The presented study focuses on the Dobšiná Ice Cave, which is worldwide unique from the speleological viewpoint, belonging to the most famous caves in Europe. During the 20th century, the research of the cave was carried out within various scientific branches. In the last years, one important part of the survey is the geodetic monitoring of the ice surface by modern laser scanning methods. Since 2020, also geophysical (georadar and microgravity) research is conducted in the Dobšiná Ice Cave. In this contribution, we present preliminary results on the present ice filling thickness, based on the interpretation of vertical radargrams and 2.5D density modelling of anomalous gravity data. Maximum thickness values from georadar measurements are more than 24.5 m in the eastern part of the cave, in the lower part of the Great Hall. Roughly estimated error of the depth determination from GPR vertical sections is at the level of ±0.5 m. Results from gravimetry apparently point to the fact that the sections with largest ice thickness could be placed rather westward to the central part of the cave. This interpretation remains questionable though, still open due to missing GPR results in the central part of the cave. We hope that future additional data and 3D density modelling will help to resolve this issue.